ANALISIS FAKTOR PENYEBAB RENDAHNYA KEDISIPLINAN SISWA KELAS 9 DALAM PEMBELAJARAN TATAP MUKA DI SMP X DI SURAKARTA (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Education is a process that aims to develop the potential of humans and gain useful knowledge for themselves later. But what happens at school, many students secretly violate and ignore the rules. Based on this phenomenon, the authors are interested to conduct research on the factors causing low discipline among 9th-grade students of SMP X in Surakarta. The method used is qualitative descriptive method. In terms of self-awareness, the students were also assessed as lacking. This is because the sanctions given are considered mild for students. The habit of a student who often do things without self-awareness and high responsibility changing their habits into bad habits. The conclusion that can be drawn, SMP X students in Surakarta are classified as having less discipline. This is evidenced by the high level of violation of school rules. The pandemic has also caused a decrease in the quality of discipline from students because it has been changed by the “new normal” which makes students carry out activities more easily at home. Keywords: S Factor Analysis, Disciplinary.